2022
DOI: 10.1007/s10608-022-10290-4
|View full text |Cite
|
Sign up to set email alerts
|

How Expectations Shape the Formation of Intrusive Memories: An Experimental Study Using the Trauma Film Paradigm

Abstract: Background Although intrusions are the hallmark symptom of posttraumatic stress disorder, there is still limited knowledge about the processes that contribute to the development of intrusions. Here, we used the well-established trauma film paradigm (TFP) to investigate how expectations about the intensity and controllability of intrusions influence their occurrence. Methods 90 healthy participants underwent the TFP before they were randomized to one of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 96 publications
1
4
0
Order By: Relevance
“…Specifically, our findings indicate that the relationship between dysfunctional general cognitions and PTSD symptoms is (partially) mediated through dysfunctional situational expectations and both types of cognitions are the link through which multiple traumatic events are associated with PTSD symptoms. The importance of situational expectations as highlighted in the present research is in line with recent predictive processing approaches to PTSD (Kube et al, 2020 ; Linson & Friston, 2019 ; Wilkinson et al, 2017 ) and with evidence from experimental work, showing that negative expectations about the occurrence of intrusive memories increase their likelihood of occurrence (Herzog et al, 2022 ; Kube et al, 2022 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Specifically, our findings indicate that the relationship between dysfunctional general cognitions and PTSD symptoms is (partially) mediated through dysfunctional situational expectations and both types of cognitions are the link through which multiple traumatic events are associated with PTSD symptoms. The importance of situational expectations as highlighted in the present research is in line with recent predictive processing approaches to PTSD (Kube et al, 2020 ; Linson & Friston, 2019 ; Wilkinson et al, 2017 ) and with evidence from experimental work, showing that negative expectations about the occurrence of intrusive memories increase their likelihood of occurrence (Herzog et al, 2022 ; Kube et al, 2022 ).…”
Section: Discussionsupporting
confidence: 88%
“…For instance, recent research has shown that negative expectations about the frequency and severity of intrusive memories (i.e. involuntary distressing thoughts or mental images in relation to traumatic events) influence the actual occurrence of intrusions (Herzog et al, 2022 ; Kube et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although meta-analyses and systematic reviews of randomized-controlled trials (RCTs; Bisson et al, 2007; Cusack et al, 2016; Ehlers et al, 2010) and practice-based studies (Herzog et al, 2022) indicate the general efficacy of psychotherapy (especially individual trauma-focused CBT in PTSD patients with moderate to large effect sizes across various settings, non-response rates and dropout rates are relatively high (Bradley et al, 2005; Schottenbauer et al, 2008). Therefore, there is space for optimizing the effects of psychotherapy in the treatment of PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, they shape perception toward the continued experience of threat, much like a self-fulfilling prophecy (Kube et al, 2020; Linson & Friston, 2019). Indeed, findings of an empirical study using the trauma film paradigm suggest that expectations might play an important role in the development of intrusive memories (Herzog et al, 2022)—the hallmark symptom of PTSD (Brewin, 2015; Iyadurai et al, 2019; Yehuda et al, 2015).…”
mentioning
confidence: 99%
“…Situation-specific expectations have been studied in different contexts, such as expectations about one's performance in a task (Kube et al, 2019b), the ability to regulate emotions (Kube et al, 2017), or the intensity and controllability of intrusions (Herzog et al, 2022). Expectations that received very limited empirical attention so far (D'Astolfo et al, 2020) are situation-specific expectations about interpersonal interactions.…”
Section: Introductionmentioning
confidence: 99%